O problema da formação humana em Freud: considerações psicanalíticas acerca do lugar do ódio na cultura contemporânea - Paula, Francirene de Sousa (2017)
This doctor research aims to interrogate the place of hate in culture from a reflection and theoretical critique of human formation in the contemporary capitalist society. It has as starting point the observation of the problem of violence is at present one of the main topics of the most various areas of human communication (domestic, academic, political, journalistic, legal, etc.). In this way, we ask ourselves: “Why are we talking so much hate and violence? What we're talking about when we talk about hatred and violence? To which they are sent?” Here are our research questions. To answer them, we have chosen as theoretical studies, Cultural Studies of Sigmund Freud where rests a Theory of the Instrument Psychic linked to a conception of culture and in which the incidence of the unconscious is remarkable: Totem and Taboo (1913), Psychology of Masses and analysis of I (1921), the Future of an Illusion (1927), malaise in the Culture (1930), Moses and monotheism (1939). In this way, we seek in the first chapter delimit theoretically the problem of human formation in the sense of culture, Kultur, having as a backdrop, the reflection of the decline of the sovereignty of the consciousness of idealism philosophical of the XIX century, based on the thinking of Marx and Freud and then Theodor Adorno and Walter Benjamin. In the second chapter, we try to identify the problem of hate in freudian theory, according to the formulations of the operation of the apparatus the psyche, presented at the first and the second topical. Finally, in the third chapter, we seek to weave considerations psychoanalytic theories on the problem of hate in the present time, in the light of the incidence of the unconscious Freudian culture, whose purpose is to contribute to the discussion of the science of education on the topic.